From Battlefield to Border: The Evolving Use of Drones in Surveillance Operations - Zhang Hua (ITEJ (Information Technology Engineering Journals), 2024)
In recent decades, drone technology has undergone rapid advancements, making it a vital tool in various surveillance operations. Initially limited to the battlefield, the use of drones has now expanded to various civilian applications, including border monitoring, law enforcement, and environmental surveillance. This shift is driven by enhancements in drone capabilities, including extended range, endurance, and sensor technology. This study employs a qualitative approach using case studies to analyze the evolution of drone usage in surveillance operations. Data were collected through literature reviews, interviews with industry experts, and analysis of reports from security and defense agencies. The study also compares the effectiveness of drone-based surveillance operations with traditional methods through statistical analysis and field operational evaluations. The findings indicate that drone usage significantly enhances the efficiency and effectiveness of surveillance operations. Drones enable wider area coverage at lower costs and reduced risks compared to conventional methods. Additionally, drones equipped with advanced sensors facilitate more accurate and real-time data collection, which is crucial in critical security situations. The study also identifies major challenges in drone usage, including regulatory issues, privacy concerns, and the integration of technology with existing systems. The evolving use of drones in surveillance operations shows great potential in enhancing security and efficiency across various sectors. However, a balanced approach between technological innovation and regulatory frameworks is necessary to address existing challenges and maximize the benefits of this technology.